Correction: High-throughput computational screening of hypothetical metal–organic frameworks with open copper sites for CO2/H2 separation. Issue 15 (30th March 2023) - Li, Mengmeng; Cai, Weiquan; Wang, Chao; Wu, Xuanjun
Abstract : Correction for 'High-throughput computational screening of hypothetical metal–organic frameworks with open copper sites for CO2 /H2 separation' by Mengmeng Li et al., Phys. Chem. Chem. Phys., 2022, 24, 18764–18776, ; https://doi.org/10.1039/D2CP01139E .